Estimation of the thyroid secondary cancer risk on the patient of standard breast external beam radiotherapy - Zeinab Momeni; Mohammad Bagher Tavakoli; Maryam Atarod (Journal of Medical Signals and Sensors, 2018)
Background: The purpose of this study was to estimate the secondary cancer risk of thyroid in standard radiotherapy methods which are commonly used for breast cancer patients. Methods: A total of 64 breast cancer patients (their age range was around 50 years old) who referred to Seyed-Al-Shohada hospital (Isfahan, Iran) were included in this study. The radiotherapy of the mentioned patients was performed using 6-MV photon beams. Dose measurements were also done using thermoluminescent dosimeters. Calculation of the risk of developing secondary cancer in thyroid was done using the Biological Effects of Ionizing Radiation Committee VII and recommended quantity of the International Radiation Protection Commission, excess relative risk. Results: The mean radiation dose to thyroid for the tangential beams, tangential field with supraclavicular (SC) field, and also a tangential field with SC field in modified radical mastectomy (MRM) were 0.883 ± 0.472, 1.512 ± 0.365, and 1.587 ± 0.37, respectively. The risk of developing secondary thyroid cancer over a period of 5 years after breast cancer therapy in the tangential, tangential with a SC field, and also tangential beam with SC field in MRM were 9.974 ± 4.318, 17.891 ± 0.365, and 18.783 ± 4.384, respectively. The mean of the measured thyroid doses in patients treated with tangent fields was significantly lower than the patients under the irradiation of the tangent fields with SC field (P < 0.001). Conclusions: Using radiation protection equipment is suggested for breast cancer patients who treated with the studied radiotherapy methods.